Analysis of the role of MYB26-interactors and genes associated with anther dehiscence - Makki, Rania (2015)
Pollen development is critical for plant reproduction. Numerous nuclear mutations affect the function of pollen resulting in male sterility. The myb26 mutant is one such male sterile mutant allele, which results in anther indehiscence. Five putative MYB26 interactive proteins were previously identified from screening an Arabidopsis stamen yeast-2-hybrid library with MYB26 as bait. These proteins include Y2H128, Y2H320, Y2560, Y2H620 and Y2H970. Transient expression of these proteins, except Y2H128 were studied in planta by infiltration of Nicotiana benthamiana leaves and all were found to be expressed in the nucleus and co-localised with MYB26. Förster Resonance Energy Transfer (FRET) was used to confirm the positive interaction between MYB26 and the Y2H320 protein. Analysis of the expression and possible function of the putative interactors was examined using SALK knockout T-DNA insertion mutants, RNAi and over-expression lines. SALK knockout lines of four Y2H genes were fully fertile and produced viable pollen despite no expression of the corresponding genes in the insertional mutants of Y2H320 and Y2H560. Independent silencing by RNAi of the other two genes, Y2H970 and Y2H128, also resulted in no alteration in plant phenotype. Transgenic plants over-expressing the Y2H genes also showed no differences in secondary thickening of anthers in endothecium compared to the wild type (Ler). Using a Prom320::GUS transgene, GUS expression was observed in the anthers, nectaries and stigmatic tissues; this pattern of Y2H320 expression corresponds to that seen for MYB26, confirming that interaction in planta is possible. The research also involved an analysis of additional four Arabidopsis male sterile mutants in the M2 and M4 generations. The phenotypes of these mutants were similar to that of the myb26 mutant, where viable pollen was evident, but anther dehiscence did not occur. These novel mutants were not rescued by Jasmonic Acid (JA) treatment. Allelism/complementation analyses indicated that the two mutants c20 and mss are alleles of myb26, whilst msak and c12 are novel mutations at different loci. Gene mapping of the MSAK gene indicated that it is located on chromosome 1. Further higher resolution genetic mapping with Simple Sequence Length Polymorphism (SSLP) molecular markers identified a closer linked marker (12.57 cM to MSAK), suggesting that the gene is located ~3.2 Mb from the start of chromosome 1. A possible candidate for MSAK gene located within the region 3.4-3.5 Mb is the transcription factor Transducin/WD40 repeat-like protein (At1g10580; located at 3.49 Mb), which is involved in pollen development. Further investigation of additional candidate genes for MSAK in the region of ~3.0-4.0 Mb of chromosome 1 that are related to male gametophyte, pollen development or belong to MYB superfamily identified a number of genes, one likely candidate is At1g10770 (located at ~3.59 Mb). Previous reports indicated that reduction of At1g10770 transcript resulted in pollen tube growth retardation, partial male sterility and reduced seed set.